(3eTcGI GdhQi aj TQM CdajI GdTgjOs - (3GdGSJQGHGOj, GdMGFQj, TQjYJeOGQ, eMeO Hf LYaQ, J (B1263(3g`s ((3eMeO ESeGYjd GdNQGSGfjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3CeG HYO, ajbhd(B... (3eMeO LYaQ GdGSJQGHGPj(B: (3deG cGf GdhGLH Ydi Gdecdajf aj CeKGd ReGffG(B...s
(3BNQgG (B:s
(3HYV GdCNHGQ LhGR UQag aj GdeUGdM GdOjfjI GdJj jNJd HOhfgG fXGe GdOjf(B. (3hGddg GdYGde HCMcGeg hdg GdMeO Ydi CSeGFg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B2(3, U(B122s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B487s
(3EjVGM Gdecfhf(B: (3L(B2(3, U(B489s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis